Današnje arabske države v učbenikih za slovenščino v osnovnih in srednjih šolah - Trškan, Danijela (Jezik in slovstvo, 2015)
The paper presents literary texts that relate to today's Arab countries and are included in the primary and secondary school textbooks for Slovenian language. Particular emphasis is placed on content in which young people can learn about history and culture, and about authors of literary works in today's Arab countries. We believe that knowledge and understanding of other countries and ways of life help young people to understand their own culture and past. The selected literary passages in Slovenian textbooks show what kind of image of today's Arab world students can gain in Slovenian lessons in primary and secondary schools of the Republic of Slovenia.
Keywords: history; zgodovinopisje; arabske države; učbeniki; Slovene; slovenščina; arabska književnost; osnovne šole; srednje šole